Acceptability of contraceptive methods in lactating mothers in a tertiary centre - Mude, Swetha; Singh, Anju; Suri, Vanita; Singla, Rimpi; Bagga, Rashmi; Jain, Vanita; Kumari, Snigdha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: High fertility rate, high maternal mortality and high infant mortality rates are the shared problems of the all the developing countries of the world. According to Directorate of Health Services surveys, 40% of women who intend to use a family planning method in the first year postpartum are not using one. Contraceptive use is negligible among postpartum women, particularly young mothers. We aimed to determine the reasons for acceptability, non-acceptability, side effects and continuation of four contraceptive methods condoms, Depotmedroxyprogesterone acetate, (DMPA), copper intrauterine contraceptive devices (IUCD), progesterone only pills (POPs) in lactating mother after 6 weeks of delivery. Methods: A total of 200 healthy nursing mothers, who needed contraception were enrolled in this prospective observational study. Women were explained about all four contraceptive methods used for the study. The reason for accepting a particular method was sought. The study participant were followed up at third and sixth month and side effects, failure rate, continuation rates, reasons for discontinuation of method were assessed. Results: The most acceptable method was condom (40.5%) followed by DMPA (31%), IUCD (20.5%) and POPs (8%). The most common reason for selection of condom was fear of side effects with other methods (66%). Long acting method like DMPA and IUCD has good continuation rate of 87% and 85% respectively. Failure of contraception was seen only with condoms (2.8%). Conclusions: This study showed condoms was most acceptable method but had failure whereas DMPA and Cu-IUCD have high continuation rate with no failure.